Novel GUCY2D mutation causes phenotypic variability of Leber congenital amaurosis in a large kindred. Issue 1 (December 2016) - Gradstein, Libe; Zolotushko, Jenny; Sergeev, Yuri; Lavy, Itay; Narkis, Ginat; Perez, Yonatan; Guigui, Sarah; Sharon, Dror; Banin, Eyal; Walter, Eyal; Lifshitz, Tova; Birk, Ohad
Abstract Background Leber congenital amaurosis (LCA) is a severe retinal degenerative disease that manifests as blindness or poor vision in infancy. The purpose of this study was to clinically characterize and identify the cause of disease in a large inbred Bedouin Israeli tribe with LCA. Methods Thirty individuals of a single kindred, including eight affected with LCA, were recruited for this study. Patients' clinical data and electroretinography (ERG) findings were collected. Molecular analysis included homozygosity mapping with polymorphic markers and Sanger sequencing of candidate genes. Results Of the eight affected individuals of the kindred, nystagmus was documented in five subjects and keratoconus in three. Cataract was found in 5 of 16 eyes. Photopic and scotopic ERG performed in 5 patients were extinguished. All affected subjects were nearly blind, their visual acuity ranged between finger counting and uncertain light perception. Assuming autosomal recessive heredity of a founder mutation, studies using polymorphic markers excluded homozygosity of affected individuals at the genomic loci of all previously known genes associated with LCA, exceptGUCY2D . Sequencing ofGUCY2D identified a novel missense mutation (c.2129C>T; p.Ala710Val) resulting in substitution of alanine by valine at position 710 within the protein kinase domain of the retina-specific enzyme guanylate cyclase 1 (GC1) encoded byGUCY2D . Molecular modeling implied that the mutation changes the conformation of the regulatory segment within the kinase styk-domain of GC1 and causes loss of its helical structure, likely inhibiting phosphorylation of threonine residue within this segment, which is needed to activate the catalytic domain of the protein. Conclusions This is the first documentation of the p.Ala710Val mutation in GC1 and the second ever described mutation in its protein kinase domain. Our findings enlarge the scope of genetic variability of LCA, highlight the phenotypic heterogeneity found amongst individuals harboring an identical LCA mutation, and possibly provide hope for gene therapy in patients with this congenital blinding disease. As the Bedouin kindred studied originates from Saudi Arabia, the mutation found might be an ancient founder mutation in that large community.